Market-Oriented Accounting Standard and Analysts’ Performance: Evidence from Brazil - Talyta Eduardo Oliveira; Antonio Carlos Coelho (BBR: Brazilian Business Review)
This research investigates if the accounting standard oriented to external users contributes to improve decision-making in the market, represented by analysts’ forecast capacity. The hypothesis is that the forecast properties for Brazilian companies’ EPS were not impacted by the change in the accounting standard. The data refer to the period 2004-2014; we employed linear multiple regression, estimated through panel data to investigate the accuracy and precision and logistic regression to scrutinize biases. Our findings indicated, with significance, that the analysts’ forecasts did not improve, thus, not rejecting the hypothesis. It was highlighted that in the convergence with the new accounting standard, the pessimistic bias was foregrounded, bringing forth analysts’ conservatism; the accuracy diminished with the new standard and the precision between periods was not altered. This research lacks depth, considering its low coefficients of determination, and in the sense of determining the causes of such behavior. An inquiry about the utilization of accounting information by analysts was also generated due to the magnitude of the forecast errors detected.